Structure-oriented dispersing agent, flaky magnesium hydroxide nano-material and preparation and application of flaky magnesium hydroxide nano-material
By using structure-oriented dispersants in the co-precipitation method to prepare sheet-like magnesium hydroxide nanomaterials, the problems of difficulty in injection in low-permeability reservoirs and low interface contact efficiency are solved, and efficient crude oil recovery and low-cost industrial production are achieved.
Patent Information
- Application Number
- CN202311091751.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-29
AI Technical Summary
Existing nanomaterials have problems such as difficulty in injection, low interface contact efficiency, and high cost in low permeability reservoirs, making it difficult to effectively improve the efficiency and recovery rate of microscopic oil washing.
The flaky magnesium hydroxide nanomaterial is prepared by using a structure-guided dispersant in the co-precipitation method, and the steric steric resistance and structural guidance of the structure-guided dispersant are used to control the growth direction of magnesium hydroxide to achieve stable preparation of flaky nanomaterials.
It realizes a low-cost, simple and stable preparation of sheet magnesium hydroxide nanomaterials, with good dispersion and interface tension reduction functions, improves crude oil recovery rate, and has industrial value.
Smart Images

Figure CN119528774A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a structure-oriented dispersant, a flaky magnesium hydroxide nano material and preparation and application thereof. Background Art
[0002] With the increasingly serious energy problems, the development of low-permeability reservoirs has also become the focus of research in the oil field. However, due to the complex pore throat structure, small pore size and large specific surface area of low-permeability reservoirs, conventional oil displacement agents have problems such as difficulty in injection. In addition, the development of natural fractures in the reservoirs causes serious heterogeneity in low-permeability reservoirs, and the remaining oil is difficult to be effectively mobilized, which also makes it difficult for conventional surfactant flooding, polymer flooding and other technologies to produce good development effects in low-permeability reservoirs.
[0003] Nanomaterials not only show good injection ability in the exploitation of low-permeability pores, but also can effectively improve the micro-oil washing efficiency by changing the wettability of the reservoir, reducing interfacial tension, and stripping the interfacial oil film. The oil recovery technology system based on nanomaterials is the key to improving the recovery rate of low-permeability reservoirs and is of great significance to the exploitation of oil and gas.
[0004] Traditional nanomaterial research focuses on one-dimensional spherical nanoparticles (such as SiO2, TiO2, Al2O3, CuO, ZnO, etc.). Spherical nanoparticles usually have advantages such as simpler manufacturing process and lower cost, but they have disadvantages such as easy aggregation and blockage, low contact efficiency with the oil-water interface, small specific surface area, few active sites, and low modification efficiency.
[0005] The two-dimensional sheet-like nanomaterials discovered in the new study have the characteristics of large specific surface area, many active sites, and high contact efficiency with the oil-water interface. However, the sheet-like nanomaterials mainly used in the current nanosheet oil displacement agents are mainly molybdenum disulfide, graphene oxide, etc., and the preparation of such nanomaterials is usually accompanied by complex processes and high costs, lacking industrial value. Compared with sheet-like nanomaterials such as graphene and molybdenum disulfide, sheet-like nanomagnesium salts have relatively low costs and higher industrial application value. At present, sheet-like nanomagnesium salts are mainly prepared by hydrothermal method and coprecipitation method: the hydrothermal method has high requirements for equipment, complex preparation process, and requires high temperature, and the reaction cost is high; although the conventional coprecipitation method is simple to operate and low in cost, the prepared nanomaterials are irregular in shape and have a wide particle size distribution, and it is impossible to obtain sheet-like nanomaterials stably and efficiently. Summary of the invention
[0006] The present invention is made in order to adopt the coprecipitation method to stably prepare sheet-like nanomaterials under low-cost conditions.
[0007] As a first aspect of the present invention, it relates to a structure-directed dispersant having the following structural formula:
[0008]
[0009] Here, R is an aliphatic hydrocarbon having 8 to 18 carbon atoms.
[0010] As a second aspect of the present invention, it relates to a method for preparing the above-mentioned structure-directed dispersant, which comprises:
[0011] S1: placing sodium alkylbenzene sulfonate in a reaction vessel and adding methanol as a solvent;
[0012] S2: At a certain reflux temperature, formaldehyde is slowly added dropwise at a certain speed to react;
[0013] S3: After the reaction is completed, the solvent is removed by reduced pressure distillation and vacuum drying to obtain the structure-directing dispersant.
[0014] Furthermore, the sodium alkylbenzene sulfonate in S1 is at least one of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, sodium hexadecylbenzene sulfonate and sodium octadecylbenzene sulfonate.
[0015] Furthermore, the molar mass ratio of the sodium alkylbenzene sulfonate to formaldehyde in S1 is 1.0:2.0-3.0.
[0016] Furthermore, the reflux temperature in S2 is 65-80° C., the rotation speed is 300 r / min, and the reaction time is 5 h.
[0017] Furthermore, the dropping speed of the formaldehyde in S2 is 2 to 4 mL / min.
[0018] As a third aspect of the present invention, it relates to a flaky magnesium hydroxide nano material, which is prepared from a magnesium source under alkaline conditions in the presence of the above-mentioned structure-directed dispersant.
[0019] As a fourth aspect of the present invention, it relates to a method for preparing the above-mentioned flaky magnesium hydroxide nanomaterial, the method comprising:
[0020] A1: Dissolve the structure-directing dispersant and magnesium source in deionized water;
[0021] A2: At a certain temperature and stirring speed, slowly add ammonia water to adjust the pH of the solution to obtain a suspension;
[0022] A3: The suspension prepared in A2 is continuously stirred and reacted at a certain temperature for a period of time, and then purified and dried to obtain the flaky magnesium hydroxide nanomaterial.
[0023] Furthermore, the mass ratio of the structure-directing dispersant to the magnesium source in A1 is 1.0:1.0-6.0.
[0024] Furthermore, the magnesium source in A1 is magnesium chloride.
[0025] Furthermore, the stirring temperature in A2 is 35-50° C., and the rotation speed is 300-500 r / min.
[0026] Furthermore, the pH value of A2 is 9-10.
[0027] Furthermore, the dropping speed of the ammonia water in A2 is 1.5 mL / min.
[0028] Furthermore, the stirring temperature in A3 is 35-50° C., and the stirring time is 180-300 min.
[0029] As a fifth aspect of the present invention, it relates to an oil displacing agent system, which comprises the above-mentioned flaky magnesium hydroxide nanomaterial.
[0030] As a sixth aspect of the present invention, it relates to the application of the above-mentioned oil displacement agent system in oil field exploitation.
[0031] When the structure-directing dispersant provided by the present invention is applied to the preparation of magnesium hydroxide by a coprecipitation method, on the one hand, as a dispersant, it plays a role in enhancing steric hindrance, can prevent the agglomeration of nano materials, and further play a role in controlling the particle size of the magnesium hydroxide nano material; on the other hand, as a structure-directing agent, it has a direct guiding effect on the growth of magnesium hydroxide, and the hydroxyl groups on the structure-directing dispersant form coordination bonds with magnesium ions, so that the structure-directing dispersant is adsorbed on the surface of magnesium hydroxide, and the structure-directing dispersant can inhibit the longitudinal growth of magnesium hydroxide crystals through the presence of benzene rings and long carbon chains on the structure-directing dispersant, and further guide the generation of magnesium hydroxide flaky morphology, thereby realizing a method for stably preparing flaky magnesium hydroxide nano materials.
[0032] The flaky magnesium hydroxide nanomaterial provided by the present invention exhibits good dispersibility in the solution, and has strong interfacial tension reduction and oil-water interface automatic adsorption functions. In addition, the structure-directed dispersant provided by the present invention itself has the characteristics of a surfactant, and can produce a synergistic effect with the synthesized flaky magnesium hydroxide nanomaterial. The nanomaterial system and the surfactant system can be compounded while the flaky magnesium hydroxide nanomaterial is synthesized, and a nano oil-displacing agent system with excellent functions can be formed by simply diluting the reaction system. The oil-displacing agent system can effectively reduce the oil-water interfacial tension and improve the crude oil recovery rate.
[0033] The method for preparing the flaky magnesium hydroxide nanomaterial is simple and stable, has a wide source of raw materials, low production cost and industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1This is a SEM image of the flaky magnesium hydroxide nanomaterial prepared in Example 5;
[0035] Figure 2 This is the SEM image of the flaky magnesium hydroxide nanomaterial prepared in Example 8. DETAILED DESCRIPTION
[0036] The following is a detailed description of the embodiments of the present invention: The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters for which specific conditions are not specified in the following embodiments are generally based on conventional conditions.
[0037] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0038] Example 1
[0039] Sodium dodecylbenzene sulfonate (3.48 g) and formaldehyde (0.6 g) were weighed in a 1:2 molar ratio. The weighed sodium dodecylbenzene sulfonate was placed in a 250 mL three-necked flask, 50 mL of methanol was added as a solvent, and formaldehyde was added dropwise at a rate of 300 r / min (dropping speed was 2.5 mL / min) while stirring at a reflux temperature of 65°C, and the reaction was carried out for 5 hours. After the reaction was completed, the solvent was removed by reduced pressure distillation and vacuum drying to obtain a viscous solid, which was a structure-directed dispersant.
[0040] Example 2
[0041] Sodium tetradecylbenzene sulfonate (3.76 g) and formaldehyde (0.75 g) were weighed in a molar ratio of 1:2.5. The weighed sodium tetradecylbenzene sulfonate was placed in a 250 mL three-necked flask, 50 mL of methanol was added as a solvent, and formaldehyde was added dropwise at a rate of 300 r / min (dropping speed was 3 mL / min) while stirring at a reflux temperature of 70°C, and the reaction was carried out for 5 hours. After the reaction was completed, the solvent was removed by reduced pressure distillation and vacuum drying to obtain a viscous solid, which was a structure-directed dispersant.
[0042] Example 3
[0043] Sodium hexadecylbenzenesulfonate (4.04 g) and formaldehyde (0.6 g) were weighed in a 1:2 molar ratio. The weighed sodium hexadecylbenzenesulfonate was placed in a 250 mL three-necked flask, and 50 mL of methanol was added as a solvent. At a reflux temperature of 75°C, formaldehyde was added dropwise at a rate of 300 r / min while stirring (the dropping speed was 3.5 mL / min), and the reaction was carried out for 5 hours. After the reaction was completed, the solvent was removed by reduced pressure distillation and vacuum drying to obtain a viscous solid, which was a structure-directed dispersant.
[0044] Example 4
[0045] Weigh sodium octadecylbenzene sulfonate (4.32 g) and formaldehyde (0.9 g) in a molar ratio of 1:3. Place the weighed sodium octadecylbenzene sulfonate in a 250 mL three-necked flask, add 50 mL of methanol as a solvent, and add formaldehyde dropwise at a rate of 300 r / min (drop speed of 4 mL / min) while stirring at a reflux temperature of 80°C, and react for 5 hours. After the reaction is completed, remove the solvent by reduced pressure distillation and vacuum drying to obtain a viscous solid, which is a structure-directed dispersant.
[0046] Example 5
[0047] Take a 250ml beaker, add 0.5g of the structure-directed dispersant prepared in Example 1, 2.0g of MgCl2 and 100ml of deionized water into the beaker, and form a dispersion by ultrasonic oscillation. Use ammonia water to adjust the pH value of the dispersion to 9. Pour the dispersion after adjusting the pH into a 250ml flask, slowly add 4g of ammonia solution (the dropping speed is 1.5mL / min) in a 35°C water bath, and stir at a rate of 300r / min. After the addition is completed, a suspension is obtained. The suspension is allowed to continue to react at a speed of 300r / min and a temperature of 35°C, and the reaction is completed after 180min. The product obtained by centrifugation is washed several times with ethanol and then dried to obtain a dry powder product, i.e., a flaky magnesium hydroxide nanomaterial.
[0048] Example 6
[0049] Take a 250ml beaker, add 0.5g of the structure-directed dispersant prepared in Example 2, 2.25g of MgCl2 and 100ml of deionized water into the beaker, and form a dispersion by ultrasonic oscillation. Use ammonia water to adjust the pH value of the dispersion to 9. Pour the dispersion after adjusting the pH into a 250ml flask, slowly add 4g of ammonia solution (the dropping speed is 1.5mL / min) in a 40°C water bath, and stir at a rate of 400r / min. After the addition is completed, a suspension is obtained. The suspension is allowed to continue to react at a speed of 400r / min and a temperature of 40°C, and the reaction is completed after 240min. The product obtained by centrifugation is washed with ethanol several times and then dried to obtain a dry powder product, i.e., a flaky magnesium hydroxide nanomaterial.
[0050] Example 7
[0051] Take a 250ml beaker, add 0.5g of the structure-directed dispersant obtained in Example 3, 2.5g of MgCl2 and 100ml of deionized water into the beaker, and form a dispersion by ultrasonic oscillation. Use ammonia water to adjust the pH value of the dispersion to 10. Pour the dispersion after adjusting the pH into a 250ml flask, slowly add 4g of ammonia solution (the dropping speed is 1.5mL / min) in a 45°C water bath, and stir at a rate of 450r / min. After the addition is completed, a suspension is obtained. The suspension is allowed to continue to react at a speed of 450r / min and a temperature of 45°C, and the reaction is completed after 240min. The product obtained by centrifugation is washed with ethanol for many times and then dried to obtain a dry powder product, i.e., a flaky magnesium hydroxide nanomaterial.
[0052] Example 8
[0053] Take a 250ml beaker, add 0.5g of the structure-directed dispersant obtained in Example 4, 3.0g of MgCl2 and 100ml of deionized water into the beaker, and form a dispersion by ultrasonic oscillation. Use ammonia water to adjust the pH value of the dispersion to 10. Pour the dispersion after adjusting the pH into a 250ml flask, slowly add 4g of ammonia solution (the dropping speed is 1.5mL / min) in a 50°C water bath, and stir at a rate of 500r / min. After the addition is completed, a suspension is obtained. The suspension is allowed to continue to react at a speed of 500r / min and a temperature of 50°C, and the reaction is completed after 300min. The product obtained by centrifugation is washed with ethanol for many times and then dried to obtain a dry powder product, i.e., a flaky magnesium hydroxide nanomaterial.
[0054] Comparative Example 1
[0055] Take a 250ml beaker, add 0.5g sodium dodecylbenzene sulfonate, 2.0g MgCl2 and 100ml deionized water into the beaker, and form a dispersion by ultrasonic vibration. Use ammonia water to adjust the pH value of the dispersion to 9. Pour the dispersion after adjusting the pH into a 250ml flask, slowly add 4g of ammonia solution (dropping speed is 1.5mL / min) in a 35°C water bath, and stir at a rate of 300r / min. After the addition is completed, a suspension is obtained. The suspension is allowed to continue to react at a speed of 300r / min and a temperature of 35°C, and the reaction is completed after 180min. The product is centrifuged, and the product is washed several times with ethanol and then dried to obtain a dry powder product, i.e., magnesium hydroxide nanomaterial.
[0056] Comparative Example 2
[0057] Take a 250ml beaker, add 0.5g polyethylene glycol 20000, 3.0g MgCl2 and 100ml deionized water into the beaker, and form a dispersion by ultrasonic vibration. Use ammonia water to adjust the pH value of the dispersion to 10. Pour the dispersion after adjusting the pH into a 250ml flask, slowly add 4g of ammonia solution (dropping speed is 1.5mL / min) in a 50℃ water bath, and stir at a rate of 500r / min. After the addition is completed, a suspension is obtained. The suspension is allowed to continue to react at a speed of 500r / min and a temperature of 50℃, and the reaction is completed after 300min. The product is centrifuged, and the product is washed several times with ethanol and then dried to obtain a dry powder product, i.e., magnesium hydroxide nanomaterial.
[0058] Test Example 1
[0059] The microscopic morphology of the magnesium hydroxide nanomaterials obtained in Examples 5 to 8 and Comparative Examples 1 and 2 was observed using an environmental scanning electron microscope. The results are shown in Table 1. The SEM image of the magnesium hydroxide nanomaterial in Example 5 is shown in Figure 1 As shown, it has a good flaky structure and a particle size of about 97nm; the SEM image of the magnesium hydroxide nanomaterial in Example 8 is as shown Figure 2 As shown, it has a good flake structure and the particle size is about 74nm.
[0060] Table 1 Characterization results of nanomaterial morphology and particle size
[0061] name Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Morphology Flake Flake Flake Flake acicular Block Particle size 97nm 89nm 91nm 74nm / / thickness 4.11nm 4.26nm 4.41nm 3.74nm / /
[0062] It can be seen from Table 1 that the magnesium hydroxide nanomaterials prepared in Examples 5 to 8 are all in a flake structure, while the magnesium hydroxide nanomaterials in Comparative Example 1 and Comparative Example 2 are in a needle-like and block-like structure, respectively.
[0063] Test Example 2
[0064] The interfacial tension performance of the magnesium hydroxide nanomaterials prepared in Examples 5 to 8 and Comparative Examples 1 and 2 was tested using an SVT20N interfacial tension meter.
[0065] First, the sample pool is filled with the magnesium hydroxide nanomaterials prepared in Examples 5 to 8, Comparative Example 1, and Comparative Example 2 to form a dispersion with a mass concentration of 0.1wt% of magnesium hydroxide nanomaterials, and then a certain volume of crude oil (Daqing Oilfield) is injected into the center of the sample pool with a micro-syringe, and the rotation speed is adjusted to 6000rpm. The image acquisition system is used to capture the change relationship of the oil droplet morphology over time, and the oil-water interfacial tension at different times is calculated according to the oil droplet morphology. After the oil-water interface is stable and unchanged, it is the oil-water interfacial tension when the oil droplet is balanced. Refer to the industry standard SYT5370-1999 of "Surface and Interface Tension Determination Method". At the same time, a surfactant sodium dodecylbenzene sulfonate is used to prepare a 0.1wt% aqueous solution as a control group. The test results are shown in Table 2.
[0066] Table 2 Interfacial tension test results
[0067]
[0068] From the analysis of Table 2, it can be seen that the flaky magnesium hydroxide nanomaterials prepared in Examples 5 to 8 can reduce the interfacial tension to 10 -1 The magnesium hydroxide nanomaterials prepared in Examples 1 and 2 can only reduce the oil-water interfacial tension to 7.29 mN / m and 10.41 mN / m, respectively. At the same time, the sodium dodecylbenzene sulfonate in the control group can reduce the oil-water interfacial tension to 1.91 mN / m, and the magnesium hydroxide nanomaterial dispersions prepared in Examples 5 to 8 show stronger interfacial activity.
[0069] Test Example 3
[0070] The magnesium hydroxide nanomaterials prepared in Examples 5 to 8 and Comparative Examples 1 and 2 were subjected to oil displacement experiments:
[0071] Using artificial core The displacement experiment was conducted, the core porosity was about 25%, the permeability was about 30mD, the core was saturated with water and then saturated with crude oil (viscosity 3.5mPa·s, 25°C), and the displacement experiment was conducted after aging for 7 days. The nanosheet mother liquor prepared in Example 5, Example 6, Example 7, Example 8, Comparative Example 1, and Comparative Example 2 was diluted to a dispersion with a nanosheet mass concentration of 0.1wt% and used as an oil displacement agent. At the same time, a surfactant sodium dodecylbenzene sulfonate was used to prepare a 0.1wt% aqueous solution as a control group.
[0072] Water was driven at a rate of 0.1 mL / min until the water cut reached 98%, and then 0.3 PV of oil-displacing agent solution was injected into the core at a rate of 0.1 mL / min, followed by subsequent water drive at a rate of 0.1 mL / min until the water cut reached 98%. The oil recovery improvement of the oil-displacing agent was calculated based on the difference between the final oil recovery and the water drive recovery. The improvement of the oil recovery of different oil-displacing agents is shown in Table 3.
[0073] Table 3 Results of enhanced oil recovery (mass fraction of oil displacement agent is 0.1wt%)
[0074]
[0075] It can be seen from Table 3 that the nano-dispersions prepared by the flaky magnesium hydroxide nanomaterials prepared in Examples 5 to 8 show a higher degree of enhanced oil recovery, indicating that under the same experimental conditions, the flaky magnesium hydroxide nanomaterials prepared in Examples 5 to 8 have better oil displacement performance than Comparative Example 1, Comparative Example 2 and sodium dodecylbenzene sulfonate when used in oil displacement agents.
[0076] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.
Claims
1. A structure-directed dispersant, characterized in that: The structure-directing dispersant has the following structural formula: Here, R is an aliphatic hydrocarbon having 8 to 18 carbon atoms.
2. The method for preparing the structure-directed dispersant according to claim 1, characterized in that: The method comprises: S1: placing sodium alkylbenzene sulfonate in a reaction vessel and adding methanol as a solvent; S2: At a certain reflux temperature, formaldehyde is slowly added dropwise at a certain speed to react; S3: After the reaction is completed, the solvent is removed by reduced pressure distillation and vacuum drying to obtain the structure-directing dispersant.
3. The method according to claim 2, characterized in that The sodium alkylbenzene sulfonate in S1 is at least one of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, sodium hexadecylbenzene sulfonate and sodium octadecylbenzene sulfonate.
4. The method according to claim 2, characterized in that The molar mass ratio of the sodium alkylbenzene sulfonate to formaldehyde in the S1 is 1.0:2.0-3.
0.
5. The method according to claim 2, characterized in that The reflux temperature in S2 is 65-80° C., the rotation speed is 300 r / min, and the reaction time is 5 h.
6. The method according to claim 2, characterized in that The drop rate of formaldehyde in the S2 is 2-4 mL / min.
7. The flaky magnesium hydroxide nanomaterial is characterized by: The flaky magnesium hydroxide nanomaterial is prepared from a magnesium source under alkaline conditions in the presence of the structure-directed dispersant described in claim 1.
8. A method for preparing a flaky magnesium hydroxide nanomaterial, characterized in that: The method comprises: A1: Dissolve the structure-directing dispersant and magnesium source in deionized water; A2: At a certain temperature and stirring speed, slowly add ammonia water to adjust the pH of the solution to a weak alkaline state to obtain a suspension; A3: The suspension prepared in A2 is continuously stirred and reacted at a certain temperature for a period of time, and then purified and dried to obtain the flaky magnesium hydroxide nanomaterial.
9. The method according to claim 8, characterized in that The mass ratio of the structure-directing dispersant to the magnesium source in A1 is 1.0:1.0-6.
0.
10. The method according to claim 8, characterized in that The magnesium source in A1 is magnesium chloride.
11. The method according to claim 8, characterized in that The stirring temperature in A2 is 35-50° C., and the rotation speed is 300-500 r / min.
12. The method according to claim 8, characterized in that The pH value of A2 is 9-10.
13. The method according to claim 8, characterized in that The dropping speed of the ammonia water in A2 is 1.5 mL / min.
14. The method according to claim 8, characterized in that The stirring temperature in A3 is 35-50° C., and the stirring time is 180-300 min.
15. An oil displacement agent system, characterized in that: The oil-displacing agent system comprises the flaky magnesium hydroxide nanomaterial according to claim 7.
16. Use of the oil displacement agent system according to claim 15 in oil field exploitation.
Citation Information
Patent Citations
Preparation method of hexagonal flaky magnesium hydroxide nanosheet
CN113371739A
Method for preparing metal compound nanoparticles
US20100178227A1
Profile control and oil displacement agent for oil reservoir and preparation method thereof
US20220064517A1